The role of regulatory necrosis in traumatic brain injury - Nie, Zhenyu; Tan, Liming; Niu, Jie; Wang, Bing (Frontiers in Molecular Neuroscience, 2022)
Traumatic brain injury (TBI) is a major cause of death and disability in the population worldwide, of which key injury mechanism involving the death of nerve cells. Many recent studies have shown that regulatory necrosis is involved in the pathological process of TBI which includes necroptosis, pyroptosis, ferroptosis, parthanatos, and Cyclophilin D (CypD) mediated necrosis. Therefore, targeting the signaling pathways involved in regulatory necrosis may be an effective strategy to reduce the secondary injury after TBI. Meanwhile, drugs or genes are used as interference factors in various types of regulatory necrosis, so as to explore the potential treatment methods for the secondary injury after TBI. This review summarizes the current progress on regulatory necrosis in TBI.